Biochemical changes and leaf photosynthesis of Erwinia mallotivora infected papaya (Carica papaya) seedlings - Y., Noor Shahida (Academic Journals, 2016)
Background and Objective: Papaya (Carica papaya) is a well-known tropical fruit consumed worldwide but its expansion is seriously impaired by many diseases including dieback caused by Erwinia mallotivora. In this study, development of dieback and changes in total phenol, total sugar, total protein, peroxidase activity, polyphenol oxidase activity and leaf photosynthesis following the inoculation of E. mallotivora on two papaya cultivars, Eksotika dan Eksotika II were reported. Methodology: Erwinia mallotivora infection (1×108 CFU mL–1, 50 μL injection) to the 8 week old seedlings at the 5th node from the apex caused dieback disease to occur as early as 3 days after inoculation. The inoculated plants were completely destroyed on day 11 after inoculation. Results: Both papaya cultivars had similar trend in their physiological and biochemical changes toward the infection. Total sugar in leaves of infected plants was higher than those in the non-infected plants, but the stem and the roots of infected plants contained markedly less sugar than those of healthy plants. Erwinia mallotivora infected tissues contained higher concentration of total phenol and total protein and these changes were coupled with higher activity of peroxidase and polyphenol oxidase. Conclusion: Plant experiencing dieback disease also had a lower leaf photosynthetic rate with reduced stomatal conductance.